High-entropy carbide ceramic as well as preparation method and application thereof
Through wet ball milling and two-step sintering technology, high entropy carbide ceramics with high fracture toughness were prepared, solving the problem of high brittleness of traditional high entropy carbide ceramics and achieving widespread application in extreme environments.
Patent Information
- Application Number
- CN202411613864.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-13
AI Technical Summary
High-entropy carbide ceramics have problems such as high brittleness and low fracture toughness, which limits their practical application in extreme fields.
By mixing metal oxide powder and carbon powder through wet ball milling, flash sintering and discharge plasma sintering, high entropy carbide ceramics with bionic "soft/hard" phase structure were prepared.
The fracture toughness of high-entropy carbide ceramics has been significantly improved, reaching 12.5MPa·m1/2±1.5MPa·m1/2, meeting the application needs in high-temperature thermal structural components, nuclear fuel cladding and other fields.
Smart Images

Figure CN119591407A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy ceramics, and in particular to a high entropy carbide ceramic and a preparation method and application thereof. Background Art
[0002] High entropy carbide ceramics have excellent properties such as high hardness, high melting point, low thermal conductivity, excellent corrosion resistance, excellent oxidation resistance, etc., and have shown very broad application prospects in extreme fields such as high-temperature thermal structural components, nuclear fuel cladding, and high-speed cutting tools. However, high entropy carbide ceramics also have inherent defects such as high brittleness and low fracture toughness, which greatly limits their practical application in extreme fields.
[0003] Beilin Ye et al. disclosed a method for toughening high entropy carbide ceramics. The fracture toughness of high entropy carbide ceramics was increased from 3.0 MPa·m by using nanosheet-induced crack deflection and nanosheet pull-out and bridging toughening mechanisms. 1 / 2 ±0.2MPa·m 1 / 2 Increased to 4.7MPa·m 1 / 2 ±0.5MPa·m 1 / 2 However, the fracture toughness of high entropy carbide ceramics is still low and cannot meet the service requirements in extreme environments (Beilin Ye, Tongqi Wen, Manh Cuong Nguyen, Luyao Hao, Cai-Zhuang Wang, Yanhui Chu. First-principles study, fabrication and characterization of (Zr 0.25 Nb 0.25 Ti 0.25 V 0.25 )C high-entropy ceramics, Acta Materials, 2019, 170: 15-23; Beilin Ye, Tongqi Wen, Kehan Huang, Cai-Zhuang Wang, Yanhui Chu. First-principles study, fabrication, and characterization of (Hf 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )C high-entropy ceramic,J.Am.Ceram.Soc.2019,102:4344-4352).
[0004] Therefore, it is of great significance to develop a high-entropy carbide ceramic with high fracture toughness. Summary of the invention
[0005] The purpose of the present invention is to provide a high entropy carbide ceramic and a preparation method and application thereof.
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing high entropy carbide ceramics comprises the following steps:
[0008] 1) Mix metal oxide powder and carbon powder and perform wet ball milling. The metal oxide powder consists of HfO 2 Powder, ZrO 2 Powder, Ta 2 O 5 Powder, Nb 2 O 5 Powder, TiO 2 Powder and Cr 2 O 3 The powder is then dried to obtain a mixed powder;
[0009] 2) pressing the mixed powder into a green body, and then covering the upper and lower surfaces of the green body with graphite paper coated with boron nitride on the upper surface, and then embedding graphite felt, and then placing the graphite felt in a protective atmosphere and connecting alternating current to flash sinter the green body, and then taking out the obtained clinker, crushing and sieving, to obtain a core-shell structure clinker powder;
[0010] 3) The graphite paper coated with boron nitride is embedded in a graphite mold, and then the core-shell structure clinker powder is loaded and pressed into a green body, and then the graphite mold is placed in a protective atmosphere and a pulse current is connected to the green body for spark plasma sintering to obtain a high entropy carbide ceramic.
[0011] Preferably, in step 1), the ratio of the total molar amount of metal atoms in the metal oxide powder to the molar amount of carbon powder is 1:1.
[0012] Preferably, in step 1) the HfO 2 Powder, ZrO 2 Powder, Ta 2 O 5 Powder, Nb 2 O 5 Powder, TiO 2 Powder and Cr 2 O 3 The particle size of the powder is 1μm to 3μm, and the purity is ≥99.9%.
[0013] Preferably, the particle size of the carbon powder in step 1) is ≤ 2 μm and the purity is ≥ 99.95%.
[0014] Preferably, the process parameters of the wet ball milling in step 1) include: the ball milling medium is anhydrous ethanol, the ball milling equipment is a planetary ball mill, the powder raw material, ZrO 2 The weight ratio of the ball to anhydrous ethanol is 1:1.8-2.2:1.0-1.5, and the ball milling time is 15h-25h.
[0015] Preferably, the pressing in step 2) is carried out at a pressure of 8 MPa to 12 MPa, and the holding time is 8 min to 12 min.
[0016] Preferably, the blank in step 2) is cylindrical, with a diameter ≤16 mm and a thickness ≤3.5 mm.
[0017] Preferably, in step 2), the graphite felt has a length of 100 mm to 120 mm, a width of 15 mm to 20 mm, and a thickness of 4.5 mm to 5.5 mm.
[0018] Preferably, the protective atmosphere in step 2) is an argon atmosphere.
[0019] Preferably, the flash sintering in step 2) specifically includes the following operations: connect the two ends of the graphite felt to an alternating current, increase the current from 0 to 60A to 75A at a rate of 2A / s to 4A / s, and then maintain for 55s to 65s, turn off the power, and cool naturally. The ultrafast carbon thermal reduction reaction brought about by flash sintering can make the high melting point component completely react to form a high entropy main phase, and the low melting point component melt for liquid phase sintering and rapid cooling. On the one hand, it can ensure that a high entropy carbide ceramic powder free of oxide impurities and fine grains is obtained, and on the other hand, it can ensure that a core-shell structure high entropy carbide ceramic powder with a low melting point component encapsulating a high melting point component is obtained.
[0020] Preferably, the comminution in step 2) is carried out by grinding.
[0021] Preferably, the mesh size of the sieve used in step 2) is 180-230 mesh.
[0022] Preferably, the pressing in step 3) is carried out at a pressure of 25 MPa to 35 MPa.
[0023] Preferably, the blank in step 3) is cylindrical with a diameter of ≤15 mm.
[0024] Preferably, the protective atmosphere in step 3) is an argon atmosphere.
[0025] Preferably, the spark plasma sintering in step 3) specifically includes the following operations: connect the graphite mold to a pulse current, increase the current from 0A to 950A to 1050A at a rate of 95A / min to 105A / min, and then continue to increase the current to 1350A to 1500A at a rate of 75A / min to 85A / min, and then maintain for 8min to 12min, turn off the power, and cool naturally. The low-voltage and high-current pulse current and the generated plasma during the spark plasma sintering process promote the rapid sintering and densification of the green body, while reducing the temperature required for densification and reducing the volatilization of low-melting-point components, and ultimately can better form a high-entropy carbide ceramic with a bionic structure.
[0026] Preferably, the spark plasma sintering in step 3) is carried out under a pressure-maintaining state, and the pressure applied to the green body is 25 MPa to 35 MPa.
[0027] A high entropy carbide ceramic is made by the above preparation method.
[0028] An application of the high entropy carbide ceramic as described above in the preparation of high-temperature structural components of aerospace vehicles, wear-resistant cutting tools, wear-resistant coatings, electromagnetic shielding materials or military armor.
[0029] The beneficial effects of the present invention are as follows: the high entropy carbide ceramics of the present invention have high fracture toughness, and the preparation method thereof has the advantages of simple operation and process flow, short reaction time, low synthesis cost, etc., and is suitable for microstructure regulation and large-scale industrial production, and has very broad application prospects in the fields of high-temperature thermal structural components, nuclear fuel cladding, high-speed cutting tools, etc.
[0030] Specifically:
[0031] 1) Inspired by the "soft / hard" alternating structure and honeycomb "grid" structure of the nacre layer of natural shells, the present invention uses transition metal oxides and carbon powder as raw materials, utilizes carbothermal reduction reaction, and prepares high-entropy carbide ceramics containing six metal elements of Hf, Zr, Ta, Nb, Ti and Cr and having a bionic "soft / hard" phase structure through a two-step method of flash sintering and spark plasma sintering, overcoming the pain points of low fracture toughness and high brittleness of traditional high-entropy carbide ceramics;
[0032] 2) The present invention first forms a core-shell structure powder with an outer "soft phase" and an inner "hard phase" by flash sintering technology, and then densifies it by spark plasma sintering, so that the "soft phase" is evenly distributed at the "hard phase" grain boundary, overcoming the problem of uneven distribution of strong and tough phases in general toughening methods;
[0033] 3) The fracture toughness of the high entropy carbide ceramic of the present invention can reach 12.5MPa·m 1 / 2 ±1.5MPa·m 1 / 2, compared with the high entropy carbide ceramics reported in the literature (4.7MPa·m 1 / 2 ±0.5MPa·m 1 / 2 ) has been improved by about 2 times, which can fully meet the high requirements for the toughness of high-entropy carbide ceramics in practical applications. It has a very broad application prospect in the fields of high-temperature structural materials of aerospace vehicles, nuclear fuel cladding, cutting and wear-resistant tools. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 2 is the XRD diagram of the core-shell structure clinker powder and high entropy carbide ceramic in Example 2.
[0035] Figure 2 This is the SEM image of the high entropy carbide ceramic in Example 2 after acid etching.
[0036] Figure 3 The SEM image and EDS element surface distribution map of the high entropy carbide ceramic in Example 2.
[0037] Figure 4 This is the SEM image of the high entropy carbide ceramic in Comparative Example 1.
[0038] Figure 5 The SEM image and EDS element surface distribution map of the high entropy carbide ceramic in Comparative Example 2. DETAILED DESCRIPTION
[0039] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0040] HfO in Examples 1 to 5 and Comparative Examples 1 to 3 2 Powder, ZrO 2 Powder, Ta 2 O 5 Powder, Nb 2 O 5 Powder, TiO 2 Powder and Cr 2 O 3 The particle size of the powder is 1μm to 3μm, and the purity is ≥99.9%.
[0041] The particle size of the carbon powder in Examples 1 to 5 and Comparative Examples 1 to 3 is ≤ 2 μm, and the purity is ≥ 99.95%.
[0042] Embodiment 1:
[0043] A high entropy carbide ceramic, the preparation method of which is as follows:
[0044] 1) 8.4 g of HfO 2 Powder, 4.9g ZrO 2 Powder, 8.8g of Ta 2O 5 Powder, 5.3g Nb 2 O 5 Powder, 3.2g TiO 2 Powder, 3.0g Cr 2 O 3 The powder and 8.9 g of carbon powder were added to a nylon ball mill, and anhydrous ethanol and zirconium oxide ball milling beads were added. The weight ratio of the powder raw material, zirconium oxide ball milling beads and anhydrous ethanol was 1:1.8:1. The nylon ball mill was then placed in a planetary ball mill and ball milled for 20 h. The anhydrous ethanol was then evaporated with a rotary evaporator to obtain a mixed powder.
[0045] 2) 2.0 g of the mixed powder was loaded into a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 8 MPa. The pressure was maintained for 10 min to form a green body (thickness of about 3 mm). Then, three through holes of about 18 mm in length were cut in the middle of the side of a graphite felt (AvCarb, model G475) with a length of 100 mm, a width of 20 mm, and a thickness of 4.75 mm. The through holes were about 3 mm apart from each other. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with boron nitride and then embedded in the graphite felt. Then, the two ends of the graphite felt were clamped with electrodes along the length direction and placed in a reactor. The reactor was closed, and the mechanical pump and the bypass valve were opened to evacuate the reactor cavity to make the vacuum pressure count value reach 10 Pa. Then, the molecular pump and the plug valve were opened to continue the vacuum treatment until the vacuum pressure count value was less than 1.2×10 -2 Pa, then slowly introduce argon until the cavity is semi-vacuumed, then turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 65A at a rate of 2A / s, and then keep it for 55s (the temperature is maintained at about 1800°C measured by an infrared thermometer), turn off the power switch, cool with the furnace, take out the clinker, grind it, and then pass it through a 200-mesh sieve to obtain a core-shell structure clinker powder;
[0046] 3) Embed the graphite paper coated with boron nitride on the surface into the graphite mold. The graphite mold is cylindrical with an inner diameter of 15.4 mm. After the graphite paper coated with boron nitride is embedded, the actual inner diameter of the graphite mold is 15.0 mm. Then, 3.5 g of core-shell structure clinker powder is loaded, and the core-shell structure clinker powder is clamped in the middle of the graphite mold by upper and lower pressure columns. Then, the graphite mold is placed in the spark plasma sintering reaction chamber, and the pressure head pressure is adjusted to 5.3 kN (30 MPa) to press the core -shell structure clinker powder is pressed into a green body, and then argon is introduced. Then the power switch is turned on to connect the upper and lower pressure columns of the graphite mold with pulse current, and the current is increased from 0 to 1000A at a rate of 100A / min, and then the current is further increased to 1350A at a rate of 80A / min. The temperature is kept at about 1550℃ for 10min (the temperature is measured by an infrared thermometer), and the power switch is turned off. Cooling with the furnace, high entropy carbide ceramics (denoted as 6HEC-1) are obtained.
[0047] According to the test, the density of the high entropy carbide ceramic (6HEC-1) in this embodiment is 99.2%, and the fracture toughness is 10.5 MPa·m 1 / 2 ±1.8MPa·m 1 / 2 .
[0048] Note:
[0049] Density: The Archimedean principle is used for testing, and the calculation formula is: Density (%) = (ρ 实际 / ρ 理论 )×100%,ρ 实际 =(m 1 ×ρ 水 ) / (m 0 -m 2 ), ρ 理论 =(N×M) / (V×N A ), where ρ 实际 is the actual density of the sample, ρ 理论 is the theoretical density of the sample, m 1 is the mass of the dry sample in air, m 0 is the mass of the sample containing saturated deionized water in air, m 2 is the mass of the sample in deionized water, N is the number of atoms in a single unit cell, M is the molar mass, V is the volume of a single unit cell, N A is Avogadro's constant.
[0050] Fracture toughness: Tested with reference to "GB / T 23806-2009 Fine Ceramics Fracture Toughness Test Method Single Edge Pre-cracked Beam (SEPB) Method".
[0051] Embodiment 2:
[0052] A high entropy carbide ceramic, the preparation method of which is as follows:
[0053] 1) 8.4 g of HfO 2 Powder, 4.9g ZrO 2 Powder, 8.8g of Ta 2 O 5 Powder, 5.3g Nb 2 O 5 Powder, 3.2g TiO 2 Powder, 5.1g Cr 2 O 3 The powder and 9.7 g of carbon powder were added to a nylon ball mill, and anhydrous ethanol and zirconium oxide ball milling beads were added. The weight ratio of the powder raw material, zirconium oxide ball milling beads and anhydrous ethanol was 1:2:1.2. The nylon ball mill was then placed in a planetary ball mill and ball milled for 20 h. The anhydrous ethanol was then evaporated with a rotary evaporator to obtain a mixed powder.
[0054] 2) 2.0 g of the mixed powder was loaded into a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 9 MPa. The pressure was maintained for 10 min to form a green body (thickness of about 3 mm). Then, three through holes of about 18 mm in length were cut in the middle of the side of a graphite felt (AvCarb, model G475) with a length of 100 mm, a width of 20 mm, and a thickness of 4.75 mm. The through holes were spaced about 3 mm apart from each other. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with boron nitride and then embedded in the graphite felt. Then, the two ends of the graphite felt were clamped with electrodes along the length direction and placed in a reactor. The reactor was closed, and the mechanical pump and the bypass valve were opened to evacuate the reactor cavity so that the vacuum pressure count value reached 10 Pa. Then, the molecular pump and the plug valve were opened to continue the vacuum treatment until the vacuum pressure count value was less than 1.2×10 -2 Pa, then slowly introduce argon until the cavity is semi-vacuumed, then turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 70A at a rate of 3A / s, and then keep it for 60s (the temperature is maintained at about 1850°C measured by an infrared thermometer), turn off the power switch, cool with the furnace, take out the clinker, grind it, and then pass it through a 200-mesh sieve to obtain a core-shell structure clinker powder;
[0055] 3) Embed the graphite paper coated with boron nitride on the surface into the graphite mold. The graphite mold is cylindrical with an inner diameter of 15.4 mm. After the graphite paper coated with boron nitride is embedded, the actual inner diameter of the graphite mold is 15.0 mm. Then, 3.5 g of core-shell structure clinker powder is loaded, and the core-shell structure clinker powder is clamped in the middle of the graphite mold by upper and lower pressure columns. Then, the graphite mold is placed in the spark plasma sintering reaction chamber, and the pressure head pressure is adjusted to 5.3 kN (30 MPa) to press the core -shell structure clinker powder is pressed into a green body, and then argon is introduced, and then the power switch is turned on to connect the upper and lower pressure columns of the graphite mold to the pulse current, and the current is increased from 0 to 1000A at a rate of 100A / min, and then the current is further increased to 1400A at a rate of 80A / min, and the temperature is kept for 10min (the temperature is maintained at about 1600℃ measured by an infrared thermometer), and the power switch is turned off, and the furnace is cooled to obtain a high entropy carbide ceramic (denoted as 6HEC-2).
[0056] Performance Testing:
[0057] 1) The X-ray diffraction (XRD) patterns of the core-shell structure clinker powder and high entropy carbide ceramic (6HEC-2) in this embodiment are as follows: Figure 1 (The powder represents the core-shell structure clinker powder, and the block represents the high entropy carbide ceramic).
[0058] Depend on Figure 1 It can be seen that 6HEC-2 contains a high entropy main phase and a honeycomb structure secondary phase, indicating that it does have a bionic "soft / hard" phase structure.
[0059] 2) The scanning electron microscope (SEM) image of the high entropy carbide ceramic (6HEC-2) in this embodiment after acid etching (the acid etching process is as follows: the sample to be tested is polished to a mirror surface with a 6000 mesh diamond grinding paste, and then the surface is acid-etched with a mixed acid solution of hydrofluoric acid, nitric acid, and deionized water in a volume ratio of 1:1:3 for 1 min, and then placed in anhydrous ethanol for ultrasonic cleaning) is as follows Figure 2 shown.
[0060] Depend on Figure 2 It can be seen that 6HEC-2 has a honeycomb bionic structure (due to the better corrosion resistance of Cr element to acid, the grains with low Cr content are obviously corroded during the corrosion of the polished surface by the mixed acid solution, and the grain boundaries with high Cr content are not obviously corroded. The resulting morphological contrast can better reflect the content, distribution and morphology of the honeycomb bionic structure).
[0061] 3) The SEM image and EDS element distribution map of the high entropy carbide ceramic (6HEC-2) in this embodiment are as follows: Figure 3 shown.
[0062] Depend on Figure 3It can be seen that Hf, Zr, Ta, Nb and Ti in 6HEC-2 are evenly distributed in the grains, and Cr is mainly distributed at the grain boundaries, indicating that the structural design of soft phase enveloping hard phase and low melting point component enveloping high melting point component is indeed realized.
[0063] 4) After testing (the testing method is the same as in Example 1), the density of the high entropy carbide ceramic (6HEC-2) in this example is 99.5%, and the fracture toughness is 12.5 MPa·m 1 / 2 ±1.5MPa·m 1 / 2 .
[0064] Embodiment 3:
[0065] A high entropy carbide ceramic, the preparation method of which is as follows:
[0066] 1) 8.4 g of HfO 2 Powder, 4.9g ZrO 2 Powder, 8.8g of Ta 2 O 5 Powder, 5.3g Nb 2 O 5 Powder, 3.2g TiO 2 Powder, 7.6g of Cr 2 O 3 The powder and 10.7 g of carbon powder were added to a nylon ball mill, and anhydrous ethanol and zirconium oxide ball milling beads were added. The weight ratio of the powder raw material, zirconium oxide ball milling beads and anhydrous ethanol was 1:2.2:1.5. The nylon ball mill was then placed in a planetary ball mill and ball milled for 20 h. The anhydrous ethanol was then evaporated with a rotary evaporator to obtain a mixed powder.
[0067] 2) 2.0 g of the mixed powder was loaded into a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 10 MPa. The pressure was maintained for 10 min to form a green body (thickness of about 3 mm). Then, three through holes of about 18 mm in length were cut in the middle of the side of a graphite felt (AvCarb, model G475) with a length of 100 mm, a width of 20 mm, and a thickness of 4.75 mm. The through holes were about 3 mm apart from each other. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with boron nitride and then embedded in the graphite felt. Then, the two ends of the graphite felt were clamped with electrodes along the length direction and placed in a reactor. The reactor was closed, and the mechanical pump and the bypass valve were opened to evacuate the reactor cavity so that the vacuum pressure count value reached 10 Pa. Then, the molecular pump and the plug valve were opened to continue the vacuum treatment until the vacuum pressure count value was less than 1.2×10 -2Pa, then slowly introduce argon until the cavity is semi-vacuumed, then turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 75A at a rate of 4A / s, and then keep it for 65s (the temperature is maintained at about 1900°C measured by an infrared thermometer), turn off the power switch, cool with the furnace, take out the clinker, grind it, and then pass it through a 200-mesh sieve to obtain a core-shell structure clinker powder;
[0068] 3) Embed the graphite paper coated with boron nitride on the surface into the graphite mold. The graphite mold is cylindrical with an inner diameter of 15.4 mm. After the graphite paper coated with boron nitride is embedded, the actual inner diameter of the graphite mold is 15.0 mm. Then, 3.5 g of core-shell structure clinker powder is loaded, and the core-shell structure clinker powder is clamped in the middle of the graphite mold by upper and lower pressure columns. Then, the graphite mold is placed in the spark plasma sintering reaction chamber, and the pressure head pressure is adjusted to 5.3 kN (30 MPa) to press the core -shell structure clinker powder is pressed into a green body, and then argon is introduced. Then the power switch is turned on to connect the upper and lower pressure columns of the graphite mold with pulse current, and the current is increased from 0 to 1000A at a rate of 100A / min, and then the current is further increased to 1450A at a rate of 80A / min. The temperature is kept at about 1650℃ for 10min (the temperature is measured by an infrared thermometer), and the power switch is turned off. Cooling with the furnace, high entropy carbide ceramics (denoted as 6HEC-3) are obtained.
[0069] After testing (the testing method is the same as that in Example 1), the density of the high entropy carbide ceramic (6HEC-3) in this example is 99.0%, and the fracture toughness is 11.4 MPa·m 1 / 2 ±2.1MPa·m 1 / 2 .
[0070] Embodiment 4:
[0071] A high entropy carbide ceramic, the preparation method of which is as follows:
[0072] 1) 8.4 g of HfO 2 Powder, 4.9g ZrO 2 Powder, 8.8g of Ta 2 O 5 Powder, 5.3g Nb 2 O 5 Powder, 3.2g TiO 2 Powder, 5.1g Cr 2 O 3 The powder and 9.7 g of carbon powder were added to a nylon ball mill, and anhydrous ethanol and zirconium oxide ball milling beads were added. The weight ratio of the powder raw material, zirconium oxide ball milling beads and anhydrous ethanol was 1:2:1.2. The nylon ball mill was then placed in a planetary ball mill and ball milled for 20 h. The anhydrous ethanol was then evaporated with a rotary evaporator to obtain a mixed powder.
[0073] 2) 2.0 g of the mixed powder was loaded into a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 9 MPa. The pressure was maintained for 10 min to form a green body (thickness of about 3 mm). Then, three through holes of about 18 mm in length were cut in the middle of the side of a graphite felt (AvCarb, model G475) with a length of 100 mm, a width of 20 mm, and a thickness of 4.75 mm. The through holes were spaced about 3 mm apart from each other. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with boron nitride and then embedded in the graphite felt. Then, the two ends of the graphite felt were clamped with electrodes along the length direction and placed in a reactor. The reactor was closed, and the mechanical pump and the bypass valve were opened to evacuate the reactor cavity so that the vacuum pressure count value reached 10 Pa. Then, the molecular pump and the plug valve were opened to continue the vacuum treatment until the vacuum pressure count value was less than 1.2×10 -2 Pa, then slowly introduce argon until the cavity is semi-vacuumed, then turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 60A at a rate of 3A / s, and then keep it for 60s (the temperature is maintained at about 1750°C measured by an infrared thermometer), turn off the power switch, cool with the furnace, take out the clinker, grind it, and then pass it through a 200-mesh sieve to obtain a core-shell structure clinker powder;
[0074] 3) Embed the graphite paper coated with boron nitride on the surface into the graphite mold. The graphite mold is cylindrical with an inner diameter of 15.4 mm. After the graphite paper coated with boron nitride is embedded, the actual inner diameter of the graphite mold is 15.0 mm. Then, 3.5 g of core-shell structure clinker powder is loaded, and the core-shell structure clinker powder is clamped in the middle of the graphite mold by upper and lower pressure columns. Then, the graphite mold is placed in the spark plasma sintering reaction chamber, and the pressure head pressure is adjusted to 5.3 kN (30 MPa) to press the core -shell structure clinker powder is pressed into a green body, and then argon is introduced, and then the power switch is turned on to connect the upper and lower pressure columns of the graphite mold to the pulse current, and the current is increased from 0 to 1000A at a rate of 100A / min, and then the current is further increased to 1400A at a rate of 80A / min, and the temperature is kept for 10min (the temperature is maintained at about 1600℃ measured by an infrared thermometer), and the power switch is turned off, and the green body is cooled with the furnace to obtain a high entropy carbide ceramic (denoted as 6HEC-4).
[0075] After testing (the testing method is the same as in Example 1), the density of the high entropy carbide ceramic (6HEC-4) in this example is 99.0%, and the fracture toughness is 10.5 MPa·m 1 / 2 ±1.8MPa·m 1 / 2 .
[0076] Embodiment 5:
[0077] A high entropy carbide ceramic, the preparation method of which is as follows:
[0078] 1) 8.4 g of HfO 2 Powder, 4.9g ZrO 2 Powder, 8.8g of Ta 2 O 5 Powder, 5.3g Nb 2 O 5 Powder, 3.2g TiO 2 Powder, 5.1g Cr 2 O 3 The powder and 9.7 g of carbon powder were added to a nylon ball mill, and anhydrous ethanol and zirconium oxide ball milling beads were added. The weight ratio of the powder raw material, zirconium oxide ball milling beads and anhydrous ethanol was 1:2:1.2. The nylon ball mill was then placed in a planetary ball mill and ball milled for 20 h. The anhydrous ethanol was then evaporated with a rotary evaporator to obtain a mixed powder.
[0079] 2) 2.0 g of the mixed powder was loaded into a mold (the mold cavity was cylindrical with a diameter of 16 mm), and the pressure was slowly increased to 9 MPa. The pressure was maintained for 10 min to form a green body (thickness of about 3 mm). Then, three through holes of about 18 mm in length were cut in the middle of the side of a graphite felt (AvCarb, model G475) with a length of 100 mm, a width of 20 mm, and a thickness of 4.75 mm. The through holes were spaced about 3 mm apart from each other. Then, the upper and lower surfaces of the green body were covered with graphite paper coated with boron nitride and then embedded in the graphite felt. Then, the two ends of the graphite felt were clamped with electrodes along the length direction and placed in a reactor. The reactor was closed, and the mechanical pump and the bypass valve were opened to evacuate the reactor cavity so that the vacuum pressure count value reached 10 Pa. Then, the molecular pump and the plug valve were opened to continue the vacuum treatment until the vacuum pressure count value was less than 1.2×10 -2 Pa, then slowly introduce argon until the cavity is semi-vacuumed, then turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 70A at a rate of 3A / s, and then keep it for 60s (the temperature is maintained at about 1850°C measured by an infrared thermometer), turn off the power switch, cool with the furnace, take out the clinker, grind it, and then pass it through a 200-mesh sieve to obtain a core-shell structure clinker powder;
[0080] 3) Embed the graphite paper coated with boron nitride on the surface into the graphite mold. The graphite mold is cylindrical with an inner diameter of 15.4 mm. After the graphite paper coated with boron nitride is embedded, the actual inner diameter of the graphite mold is 15.0 mm. Then, 3.5 g of core-shell structure clinker powder is loaded, and the core-shell structure clinker powder is clamped in the middle of the graphite mold by upper and lower pressure columns. Then, the graphite mold is placed in the spark plasma sintering reaction chamber, and the pressure head pressure is adjusted to 5.3 kN (30 MPa) to press the core -shell structure clinker powder is pressed into a green body, and then argon is introduced, and then the power switch is turned on to connect the upper and lower pressure columns of the graphite mold to the pulse current, and the current is increased from 0 to 1000A at a rate of 100A / min, and then the current is further increased to 1500A at a rate of 80A / min. The temperature is kept for 10 minutes (the temperature is measured by an infrared thermometer and maintained at about 1700°C), and the power switch is turned off. Cool with the furnace to obtain high entropy carbide ceramics (denoted as 6HEC-5).
[0081] After testing (the testing method is the same as in Example 1), the density of the high entropy carbide ceramic (6HEC-5) in this example is 99.4%, and the fracture toughness is 9.6 MPa·m 1 / 2 ±1.5MPa·m 1 / 2 .
[0082] Comparative Example 1:
[0083] A high entropy carbide ceramic (denoted as 6HEC-6) is exactly the same as Example 2 except that the current in step 2) is adjusted from "70A" to "55A" and the size of the graphite felt in step 2) is adjusted to "100mm long, 25mm wide, and 4.75mm thick" during preparation.
[0084] Performance Testing:
[0085] 1) The SEM image of the high entropy carbide ceramic (6HEC-6) in this comparative example is as follows Figure 4 shown.
[0086] Depend on Figure 4 It can be seen that the density of 6HEC-6 is low. The reason is that the current in step 2) is too low and the graphite felt is too wide, resulting in the actual reaction temperature being unable to completely carry out the carbon thermal reduction reaction. In the subsequent experimental steps, continuous gas generation leads to the formation of a large number of microscopic pore structures inside the ceramic, thereby reducing the density of the ceramic.
[0087] 2) After testing (the testing method is the same as that of Example 1), the density of the high entropy carbide ceramic (6HEC-6) in this comparative example is 91.2%, and the fracture toughness is 2.7 MPa·m 1 / 2 ±0.5MPa·m 1 / 2 .
[0088] Comparative Example 2:
[0089] A high entropy carbide ceramic (denoted as 6HEC-7) is prepared in the same manner as in Example 2 except that the current in step 3) is adjusted from "1400A" to "1550A (temperature maintained at about 1750°C)".
[0090] Performance Testing:
[0091] 1) The SEM image and EDS element distribution map of the high entropy carbide ceramic (6HEC-7) in this comparative example are as follows: Figure 5 shown.
[0092] Depend on Figure 5 It can be seen that 6HEC-7 does not contain a honeycomb bionic structure. The reason is that the current in step 3) is too large and the spark plasma sintering reaction temperature is too high, causing the low melting point component to volatilize at high temperature and react with the graphite mold.
[0093] 2) After testing (testing method is the same as Example 1), the density of the high entropy carbide ceramic (6HEC-7) in this comparative example is 99.0%, and the fracture toughness is 2.5 MPa·m 1 / 2 ±0.6MPa·m 1 / 2 .
[0094] Comparative Example 3:
[0095] A high entropy carbide ceramic (denoted as 6HEC-8) is prepared by adjusting the operation of step 3) to "put 1.2 g of core-shell structure clinker powder into a mold (the mold cavity is cylindrical and has a diameter of 10 mm), slowly pressurize to 8 MPa and hold the pressure for 5 minutes to prepare a clinker blank, then cut a through hole of about 12 mm in the middle of the side of a graphite felt (AvCarb, model G475) with a length of 100 mm, a width of 12 mm and a thickness of 4.75 mm, cover the upper and lower surfaces of the clinker blank with graphite paper coated with boron nitride and then embed the graphite felt, then clamp the two ends of the graphite felt with electrodes along the length direction and place it in a reactor, close the reactor, open the mechanical pump and the bypass valve to evacuate the reactor cavity so that the vacuum pressure count value reaches 10 Pa, then open the molecular pump and the plug valve to continue the vacuum treatment until the vacuum pressure count value is less than 1.2×10 -2 Pa, and then slowly introduce argon until the cavity is semi-vacuumed, then turn on the power switch to connect the two ends of the graphite felt to AC, increase the current from 0 to 60A at a rate of 2A / s, and then maintain for 60s (the temperature is maintained at about 1900°C measured by an infrared thermometer), turn off the power switch, and cool with the furnace "(i.e., change to flash sintering), the rest is exactly the same as Example 2.
[0096] After testing (SEM test), the density of 6HEC-8 is relatively low. The reason is that the flash sintering method used in step 3) is pressureless sintering. Pressureless sintering cannot fully densify the sample in a short time, which reduces the density of the ceramic.
[0097] After testing (the testing method is the same as that of Example 1), the density of the high entropy carbide ceramic (6HEC-8) in this comparative example is 95.0%, and the fracture toughness is 6.7 MPa·m 1 / 2 ±0.9MPa·m 1 / 2 .
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing high entropy carbide ceramics, characterized in that: The following steps are involved: 1) mixing metal oxide powder and carbon powder for wet ball milling, wherein the metal oxide powder consists of HfO2 powder, ZrO2 powder, Ta2O5 powder, Nb2O5 powder, TiO2 powder and Cr2O3 powder, and then drying to obtain a mixed powder; 2) pressing the mixed powder into a green body, and then covering the upper and lower surfaces of the green body with graphite paper coated with boron nitride on the upper surface, and then embedding graphite felt, and then placing the graphite felt in a protective atmosphere and connecting alternating current to flash sinter the green body, and then taking out the obtained clinker, crushing and sieving, to obtain a core-shell structure clinker powder; 3) The graphite paper coated with boron nitride is embedded in a graphite mold, and then the core-shell structure clinker powder is loaded and pressed into a green body, and then the graphite mold is placed in a protective atmosphere and a pulse current is connected to the green body for spark plasma sintering to obtain a high entropy carbide ceramic.
2. The method for preparing high entropy carbide ceramics according to claim 1, characterized in that: Step 1) The ratio of the total molar amount of metal atoms in the metal oxide powder to the molar amount of carbon powder is 1:
1.
3. The method for preparing high entropy carbide ceramics according to claim 1 or 2, characterized in that: The particle sizes of the HfO2 powder, ZrO2 powder, Ta2O5 powder, Nb2O5 powder, TiO2 powder and Cr2O3 powder in step 1) are all 1μm to 3μm, and the purity is ≥99.9%; the particle size of the carbon powder in step 1) is ≤2μm, and the purity is ≥99.95%.
4. The method for preparing high entropy carbide ceramics according to claim 1 or 2, characterized in that: Step 1) The process parameters of the wet ball milling include: the ball milling medium is anhydrous ethanol, the ball milling equipment is a planetary ball mill, the weight ratio of the powder raw material, ZrO2 balls and anhydrous ethanol is 1:1.8~2.2:1.0~1.5, and the ball milling time is 15h~25h.
5. The method for preparing high entropy carbide ceramics according to claim 1, characterized in that: Step 2) The pressing is carried out under a pressure of 8MPa to 12MPa, and the holding time is 8min to 12min; Step 2) The blank is cylindrical, with a diameter of ≤16mm and a thickness of ≤3.5mm; Step 2) The graphite felt has a length of 100mm to 120mm, a width of 15mm to 20mm, and a thickness of 4.5mm to 5.5mm.
6. The method for preparing high entropy carbide ceramics according to claim 1 or 5, characterized in that: Step 2) The flash sintering specifically includes the following operations: connecting both ends of the graphite felt to alternating current, increasing the current from 0 to 60A-75A at a rate of 2A / s-4A / s, maintaining the current for 55s-65s, disconnecting the power, and cooling naturally.
7. The method for preparing high entropy carbide ceramics according to claim 1, characterized in that: Step 3) The pressing is carried out under a pressure of 25MPa to 35MPa; Step 3) The blank is cylindrical with a diameter of ≤15mm.
8. The method for preparing high entropy carbide ceramics according to claim 1 or 7, characterized in that: Step 3) The spark plasma sintering specifically includes the following operations: connecting the graphite mold to a pulse current, increasing the current from 0 A to 950 A to 1050 A at a rate of 95 A / min to 105 A / min, and then increasing the current to 1350 A to 1500 A at a rate of 75 A / min to 85 A / min, and then maintaining the current for 8 min to 12 min, turning off the power, and cooling naturally.
9. A high entropy carbide ceramic, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the high entropy carbide ceramic according to claim 9 in the preparation of high temperature structural parts of aerospace vehicles, wear-resistant cutting tools, wear-resistant coatings, electromagnetic shielding materials or military armor.
Citation Information
Patent Citations
Preparation method for fuel pellet based on nano uranium dioxide or nano uranium dioxide compound
CN108335768A
Preparation method of high-density silicon carbide ceramic composite material
CN112279650A
High-entropy carbide ceramic powder as well as preparation method and application thereof
CN115286389A
Instantaneous ceramic sintering device and sintering method
CN116558297A
High-entropy boride ceramic material as well as preparation method and application thereof
CN117105671A